Quality declared planting material (QDPM): Standards and inspection procedures, Nigeria - Abidin, P.E. (International Potato Center, 2016)
This protocol is part of the project framework and represents one of the outputs / outcomes of the CIP-led project “Jumpstarting orange-fleshed sweetpotato in West Africa through diversified markets.” Tested and executed in 2016, the protocol can be used for anybody who intends to commercialize the sweetpotato planting materials.